3 - Gender Division of Labour and Women’s Decision-Making Power in Rural Households in Cameroon - Sikod, Fondo (Africa Development, 2007)
In most rural areas of Cameroon, women are incorporating a market-oriented dimension to their farming activities. This is an improvement from years before when food crop farming was almost exclusively for household consumption. This additional focus on food crop farming is mainly as a result of the need to supplement household incomes following the drop in salaries which came as a result of the economic crisis Cameroon and many African countries have been facing since the 1980s. Nominal incomes for salary earners in Cameroon, mostly men, were slashed by over 60 per cent in the early 1990s (Tchoungui et al., 1995). The agricultural sector was not spared either. Most of Cameroon’s foreign earn- ings come from agricultural commodities – cocoa, coffee, cotton, whose produc- tion is largely in small-holdings owned mostly by men. In the 1980s, world prices for these commodities collapsed, and of course, the incomes of the small-hold- ers dropped drastically. The burden of making up for this shortfall within house- holds was placed on the backs of women. Considering that decision-making seems to be based on, among other factors, economic power, income earnings is likely to confer a certain degree of decision-making power on women (Ngome 2003). This paper looks at how change in the gender division of labour impacts women’s decision-making power, and whether the traditional division of labour, which gives women very little access to labour-augmenting re ources, leads to an inefficient allocation of resources that retard development.